Description of a new Tiger Snake (Colubridae, Telescopus) from south-western Africa - Haacke, Wulf D. (Zootaxa, 2013)
Telescopus finkeldeyi sp. nov. is described from western central to northern Namibia and south-western Angola. Its maximum size is less than that of the other three taxa occurring in southern Africa. It is further distinguished by its fairly variable colour pattern. Although the number of ventrals and the undevided anal scale are similar to that of T. beetzii, the presence of 19 scale rows around the middle differs from the 21 rows of T. beetzii.